Establishment of a p-nitrophenol oxidation-based assay for the analysis of CYP2E1 activity in intact hepatocytes in vitro - Mahli, Abdo; Thasler, Wolfgang Erwin; Hellerbrand, Claus (Toxicology Mechanisms and Methods, 2019)
CYP2E1 is a mammalian cytochrome P450 enzyme, which oxidizes a structurally diverse class of endogenous and exogenous (xenobiotic) compounds. Best studied is the role of CYP2E1 in phase I metabolism of xenobiotics including alcohol. CYP2E1 metabolizes ethanol and is active in generating reactive oxygen species (ROS) and subsequent oxidative stress in the hepatic tissues. Several studies have shown and discussed the importance of CYP2E1 in the hepatotoxic actions of alcohol. However, the vast majority assessed the CYP2E1 activity only in isolated microsomes. Here, we aimed to develop and optimize a fast and easy method to assess alcohol-induced CYP2E1 activity in hepatocytes in vitro applying oxidation of para-nitrophenol to para-nitrocatechol as specific substrate probe. Using hepatoma cells with and without stable CYP2E1 expression and primary human hepatocytes, we established specific methodology to assess CYP2E1 catalytic activity and its induction by ethanol in a small number of cells and in a very short time.
CRIS-Team WoS Importer:2019-04-12